2010
DOI: 10.1002/bdrb.20224
|View full text |Cite
|
Sign up to set email alerts
|

Korean red ginseng extract does not cause embryo‐fetal death or abnormalities in mice

Abstract: Considerable developmental toxicities of KRGE, even at the upper-limit dose, were not observed in mice. These results might be due to the negligible blood concentrations of ginsenosides in their original forms following oral administration, suggesting that in vitro experiments to assess the effects of ginsenosides on embryotoxicity may not reliably explain the risks of ginsenosides to in vivo embryo-fetal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…Shin et al . [61] evaluated the toxicity of Korean red ginseng against embryonic implantation and mortality and fetal body weight gain at doses of up to 2,000 mg/kg/d, which is approximately 200 fold greater than the clinical dose recommended by the Korean Food and Drug Administration. The authors concluded that the consumption of ginseng did not cause embryo-fetal death or abnormalities.…”
Section: Summary Of the Major Findings Of Selected Publicationsmentioning
confidence: 99%
“…Shin et al . [61] evaluated the toxicity of Korean red ginseng against embryonic implantation and mortality and fetal body weight gain at doses of up to 2,000 mg/kg/d, which is approximately 200 fold greater than the clinical dose recommended by the Korean Food and Drug Administration. The authors concluded that the consumption of ginseng did not cause embryo-fetal death or abnormalities.…”
Section: Summary Of the Major Findings Of Selected Publicationsmentioning
confidence: 99%
“…These negative in vitro outcomes with whole extracts contrast the findings from in vivo studies investigating the influence of Red Korean Ginseng treatment two weeks before mating and throughout gestation on pregnancy in the mouse (Shin et al, 2010). Due to these discrepancies in outcomes it was essential to conduct in vivo experiments using NAG on pregnancy and post-partum development in the mouse.…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, Lee et al (2008) found treatment of early rat embryos with individual ginsenosides resulted in either no significant change to the morphological scores or improvements. In addition, very recent in vivo studies have shown that when up to 2000 mg/kg/day (≈200 times the recommended clinical dose) of Korean Red Ginseng extract was administered to female mice, maternal weight, feeding, embryonic implantation and fetal growth were not significantly affected (Shin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several constituents of red ginseng have been reported to regulate proliferation and migration and to protect oxidative stress-mediated damage in human endothelial cells [38,39]. There is evidence demonstrating the presence of major ginsenosides including Rb1 and Rg1 in KRG water extract [40]. Thus, these components could also contribute to the diverse retinue of protective actions of KRG.…”
Section: Discussionmentioning
confidence: 99%